Investigation on influential factors on chloride concentration index of cement-based materials by pore solution expression method. (20th January 2020) - Hu, Xiang; Shi, Caijun; Zhu, Deju; de Schutter, Geert
Highlights: Effects of different factors on chloride concentration index ( N c ) of cement paste are studied. Zeta potential, thickness and chloride distribution of EDL are investigated. The relationship between N c and properties of EDL are modeled and studied. Abstract: In this study, the effects of different factors on chloride concentration index ( N c ) of cement paste were studied. The factors including chloride concentration in soaking solution, slag replacement, external applied voltage and cation ions of soaking solution were all studied from the electrical double layer (EDL) properties point of view. Zeta potential and proton Nuclear Magnetic Resonance ( 1 H NMR) measurements were conducted to investigate the properties of electrical double layer for cement paste specimens and their effects on the value of chloride concentration index. The results showed that these factors all impacted effects on chloride concentration in electrical double layer and chloride concentration index. The properties of electrical double layer including chloride distribution and thickness of electrical double layer mainly controlled the phenomenon of "chloride concentrate" and value of chloride concentration index. As the increase of zeta potential and electrical double layer thickness, the content of chloride ions in electrical double layer and the value of chloride concentration index gradually increased.